Time-to-treatment of diffuse large B-cell lymphoma in São Paulo - Xavier, Flávia Dias (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2014)
OBJECTIVE: Diffuse large B-cell lymphoma is the most common type of non-Hodgkin lymphoma, accounting for nearly 50% of the cases in the Hematology Department of the Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo and Instituto do Câncer do Estado de São Paulo. The treatment outcome is influenced by age, abnormal lactate dehydrogenase levels, extranodal infiltration, the disease stage and the patient's performance status. In this study, we sought to report the time-to-treatment of diffuse large B-cell lymphoma in São Paulo's public health system network and its impact on patient outcomes. METHODS: We prospectively followed a cohort of 42 consecutive patients with de novo diffuse large B-cell lymphoma between 2008 and 2012. RESULTS: Our patients had more advanced disease than that reported in the literature (61.9% vs. 46%). In São Paulo's public health system network, it took an average of 7.4 months for a diagnosis to be made and an additional 1.4 months to obtain an appointment with a specialist. Once at our Hematology Department, it took less than 20 days for staging, confirmation of the diagnosis and treatment initiation. An interval from signs or symptoms to treatment of more than 6 months was associated with inferior progression-free survival in 3 years (p = 0.049). CONCLUSION: A delay in the diagnosis of diffuse large B-cell lymphoma is a public health problem and may be associated with worse progression-free survival.